DEVELOPMENT OF CAROTENE PRODUCTION KINETICS MODEL FROM OIL PALM EMPTY FRUIT BUNCH - Natasya
Having healthy eyes is closely related to vitamin A consumption. Vitamin A can be obtained in the form of ?-carotene, where 6 ?g ?-carotene can produced 1 ?g RE of vitamin A. Production of ?-carotene using Neurospora sp. can produced a high number of carotenoids and oil palm empty fruit bunches (OPEFB) has potential to be used as a substrate. The purposes of this research are to determine the kinetic parameters of ?-carotene formation and growth of Neurospora sp. through simulation of experimental data, as well as compiling and using the kinetic model of ?-carotene formation to determine the optimum conditions for ?-carotene production. The research begins by determining the equations used in modeling the kinetics of ?-carotene production, such as cell growth rate, oxygen consumption rate, and product formation rate. Solid phase fermentation of EFB substrate with variations in air humidity and duration of fermentation is carried out to determine the optimum conditions for ?-carotene production and obtain oxygen consumption data. Through this data, we can obtain cell growth profile. The fermentation product was extracted through maceration, and the extract is analyzed to obtain the concentration, yield, and rate of ?-carotene formation. In this research, a simulation is done to determine the growth kinetics parameters of Neurospora sp. and the formation of ?-carotene through experimental data. Based on the simulation, the values of ? and ? constants are 8 x 10-5 and 8 x 10-7, respectively, so that the production of ?-carotene is mixed-growth associated. The kinetic parameters are used in building the kinetics model for the formation of ?-carotene and it is known that the increase in inoculum and medium concentration, also the duration of fermentation increased the production of ?-carotene. In experimental validation, the fermentation is performed for 5 days, by adding more 20 grams of initial inoculum and 5 grams of glucose in the medium. Through the optimization process, the obtained value of ?-carotene was 0.014 mg ?-carotene/g EFB with an increase of 27.27% from the fermentation result before optimization.